The Importance of Financial Roles in Optimizing Laboratory Facilities - Ucik Fauziah; Hidayatulloh Hidayatulloh; Renny Oktafia (International Consortium of Education and Culture Research Studies, 2020)
The purpose of this study is to examine the important role of finance in optimizing laboratory facilities. The research is using a qualitative-descriptive study with interview methods and triangulation techniques. Interviews were conducted with the Principal, Deputy Principal for Curriculum, Deputy Principal for Facilities and Infrastructure, and Treasurer of educational institutions. The results of this activity illustrate that the development of funding for educational institutions is expected to increase the ability of students in learning. One of them is the development of laboratory facilities.